Students’ Perspective And Experience In Learning English Hospitality At Hotel And Cruise Line Hsc-Atc College - Saiful Anwar (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
English nowadays was an essential language in many specific purposes. For example in English for hospitality, it was needed as the medium to talk with guest/tourists from all over the world. The purpose of this study was to know the students’ experience in studying English hospitality at hotelier and cruise line HSC ATC College. The method of this study was narrative inquiry. As stated by Ary (2010) that the focus of narrative research was to tell stories from some individual about their lives. It was underlined that it could be from their experience while studying in school and college. The data collection of this study was interview. The subjects were the three students who were learning English at HSC ATC College. The findings reveal that students were exited with the learning activity in class and motivated to study English well that correlate to dialogues in hotel although there were still some aspects that make students worry in speaking English. It was because the lack of vocabulary and pronouncing words. The cause of misunderstanding was errors in pronouncing words. But, based on their experiences that they haved spirit to study English for bright future.